(untitled) - Sebesta, Robert W. (Boston, 2002)
From the Publisher: This best-selling book, now in its fourth edition, provides a wide-ranging and in-depth discussion of programming language concepts. As in previous editions, the author describes fundamental concepts of programming languages by presenting design issues of the various language constructs, examining the design choices for these constructs in a few common languages, and critically comparing the design alternatives. The book covers the most widely used methods of syntax description and introduces the most common approaches to describing the semantics of programming languages. Discussions of implementation methods and issues are integrated throughout the book.
Keywords: Programming languages,Ngôn ngữ lập trình; Electronic computers,Máy tính điện tử